IMPLEMENTATION OF ELASTIC AES - Swati P. More; Dr.V.R.Ghorpade (International Journal of Innovations in Engineering Research and Technology, 2021)
Elastic block cipher, allows to “stretching” the supported block size of block cipher up to a length double the original block size, while increasing the computational workload proportionally to the block size. We opt for the first method for creating an elastic block cipher from an existing block cipher. Our intent is not to design a newad-hoc cipher. But to systematically build upon existing block ciphers. Our method uses the round function from an existing block cipher. Allowing us to treat the round function of the original cipher as a black box and reuse its properties. This results in the security of the elastic version of a cipher being directly related to that of the original cipher. Our method is designed to enable us to form a reduction between the elastic and the original versions of the cipher. Using this reduction, we prove that the elastic version of a cipher is secure against a key-recovery attack if the original cipher is secure against such attacks.